Ovarian Fibromas and Fibrothecomas: Sonographic Correlation With Computed Tomography and Magnetic Resonance Imaging: A 5‐Year Single‐Institution Experience. (1st January 2013) - Yen, Philip; Khong, Kathleen; Lamba, Ramit; Corwin, Michael T.; Gerscovich, Eugenio O.
Abstract : Objectives: To evaluate imaging characteristics of ovarian fibromas and fibrothe‐comas and to identify select clinical markers and imaging features to help in their diagnosis. Methods: Over a 5‐year period, 18 of 29 women with histologically proven fibromas or fibrothecomas underwent sonography, computed tomography (CT), or magnetic resonance imaging (MRI). On review of the images, tumor size, solid component characteristics, and cystic components were evaluated. Age, cancer antigen 125 (CA‐125), and Meig syndrome were assessed. Results: Eleven fibrothecomas and 7 fibromas were evaluated. Sonography was performed for 15 tumors, CT for 9, and MRI for 6. Mean age was 52.6 (range, 13–82) years. Mean tumor size was 8.8 (range, 2–18) cm. Seventy‐two percent of the tumors were solid, and 28% had cystic components. On sonography, the solid components were isoechoic or hypoechoic compared to the uterus. On CT with contrast, 2 of 8 lesions (25%) showed enhancement. On T1‐weighted MRI, 5 lesions (83%) showed an isointense signal, and 1 (17%) showed a hyperintense signal compared to the myometrium. On T2‐weighted MRI, 4 of 6 lesions (67%) were hypointense; 1 (16.5%) was isointense; and 1 (16.5%) was hyperintense. Elevated CA‐125 was present in 5 of 29 patients (28%). One had Meig syndrome. Conclusions: For a cystic adnexal mass where the primary consideration is commonly an epithelial tumor, the possibility of a cystic stromal tumor should also be considered. Unlike previous studies reporting both T1 and T2 hypointensity, fibrothecomas and fibromas can also show T1 and T2 isointensity and, exceptionally, hyperintensity. Vascularity, shown by Doppler flow and MRI and CT enhancement, is a characteristic of some fibromas and fibrothecomas. Although CA‐125 is elevated in some patients, a true correlation is difficult to assess. Meig syndrome is infrequent.